2004
DOI: 10.1103/physreve.70.036602
|View full text |Cite
|
Sign up to set email alerts
|

Saturation-induced coherence loss in coherent backscattering of light

Abstract: We use coherent backscattering (CBS) of light by cold Strontium atoms to study the mutual coherence of light waves in the multiple scattering regime. As the probe light intensity is increased, the atomic optical transition starts to be saturated. Nonlinearities and inelastic scattering then occur. In our experiment, we observe a strongly reduced enhancement factor of the coherent backscattering cone when the intensity of the probe laser is increased, indicating a partial loss of coherence in multiple scatterin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
106
1
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(122 citation statements)
references
References 25 publications
13
106
1
2
Order By: Relevance
“…Experimental studies on cold Sr atoms revealed a rapid decrease of the CBS interference contrast with increasing intensity of the injected laser field, as a consequence of the saturation of the laser-driven atomic transition [8]. A much weaker sensitivity of the quality of the CBS signal was observed for Rb atoms [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies on cold Sr atoms revealed a rapid decrease of the CBS interference contrast with increasing intensity of the injected laser field, as a consequence of the saturation of the laser-driven atomic transition [8]. A much weaker sensitivity of the quality of the CBS signal was observed for Rb atoms [9].…”
Section: Introductionmentioning
confidence: 99%
“…We address a regime of multiple scattering which is relatively simple from the theoretical point of view: scattering by an optically thin atomic medium, where double scattering provides the dominant contribution to the CBS signal [10,15]. It is in this double scattering regime where the first observation of a CBS reduction due to the saturation of atomic dipole transitions was reported [8].…”
Section: A Master Equation For Two Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for degenerate (e.g., in rubidium atoms) and non-degenerate (e.g. in strontium atoms [8]) transitions alike, increasing the intensity of the incident laser field leads to atomic saturation accompanied by nonlinear (multi-photon) inelastic scattering processes [9] reducing the interference contrast in CBS [10].…”
Section: Introductionmentioning
confidence: 99%
“…While a thorough theory of CBS of light from degenerate atoms in the regime of elastic scattering already exists [11,12], a theory of CBS from saturated atoms is still in a rudimentary state, several years after the "saturation" experiments with strontium [10] and rubidium [13] atoms. The main obstacle for developing such a theory is that CBS becomes a multi-wave interference effect in the nonlinear scattering regime [14,15], with more than two interfering amplitudes.…”
Section: Introductionmentioning
confidence: 99%